2015
DOI: 10.1113/jphysiol.2014.287144
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal muscle and tendon structure and function following genetic inactivation of myostatin in rats

Abstract: Key pointsr Myostatin is an important regulator of muscle mass and a potential therapeutic target for the treatment of diseases and injuries that result in muscle atrophy.r Targeted genetic mutations of myostatin have been generated in mice, and spontaneous loss-of-function mutations have been reported in several species. The impact of myostatin deficiency on the structure and function of muscles has been well described for mice, but not for other species.r We report the creation of a genetic model of myostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 54 publications
(118 reference statements)
0
40
0
Order By: Relevance
“…16, 25 The general techniques and methodologies in this study have been previously published and are provided in brevity in the current manuscript. 16, 17, 27, 30 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16, 25 The general techniques and methodologies in this study have been previously published and are provided in brevity in the current manuscript. 16, 17, 27, 30 …”
Section: Methodsmentioning
confidence: 99%
“…27, 33 Briefly, 100 mg of muscle was homogenized in Tissue Protein Extraction Reagent (Thermo Scientific, Rockford, IL, USA) supplemented with a protease and phosphatase inhibitor cocktail (Thermo Scientific), homogenized, spun at 12,000 × g for 10 min, and the supernatant was collected and stored at −80°C until use. A BCA protein assay (Thermo Scientific) was used to determine protein content, and the relative abundance of phosphorylated p38 MAPK (phosphorylation at Thr 180 and Tyr 182 residues) from 50 μg of total protein was analyzed using a Milliplex-p38 phospho protein magnetic bead assay (EMD Millipore Corporation, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] For example, the secretion of GDF-8 from myogenic cells regulates the structure and function of tendon tissues in both prenatal and postnatal development. 18,30,31 Actually, our recent study revealed that the mechanical strength of in vivo engineered tendons could be significantly reduced when myocytes and fibroblasts were isolated by differential adhesion rates (data not shown), and this thus becomes our future direction for exploring the detailed mechanism in muscle-derived cell engineered tendon regeneration and maturation.…”
Section: Discussionmentioning
confidence: 90%
“…Myostatin has the larger impact on muscle mass than any other single signaling molecule, and it appears to regulate muscle fiber size by interacting with both the protein synthesis and degradation pathways in muscle fibers (Mendias et al, 2015). It has been demonstrated that increased levels of myostatin is due to upregulation of the muscle-specific E3 ligases, Atrogin-1 and muscle ring finger protein 1 (MuRF1) through Smad 3 mediated up regulation of Atrogin-1 and forkhead box O1 (Lokireddy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%